Critical Analysis of the Elimination of Pancasila Education in Government Policy Number 57 of 2021 concerning National Education Standards - Suwaibatul Aslamiyah; Purwanto Purwanto; Siti Choiriyah; Ida Royani (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
All elements of life in the unitary state will not be separated from the national legal system, in the theory of legislation it is known as the statutory hierarchy, this contains the content that all the rules under it are used as implementing rules for the rules above and there are no conflicting rules between the two. Recently, the public was surprised by the government's policy through Government Regulation Number 57 of 2021 regarding the elimination of Pancasila and Indonesian language education as compulsory curriculum content. Whereas government regulations are used as derivatives of the law on the national education system and the law on higher education. The research method used is the use of normative juridical critical analysis methods and viewed from various points of view in giving disapproval of government policies through Government Regulation Number 57 of 2021 precisely in Article 40 Paragraphs 2 and 3. The results of this study are to present 3 basic reasons why it is necessary to include Pancasila in the Government Regulation, namely First, the need to consider the previous regulations, second, the need for the formulation of this policy through an open political process, third, the need to review it from the point of view of Education Reformulation, both philosophically and ideologically. Thus, it is very necessary to review this legal product so that it is relevant to the law as the parent law.